A novel approach for monitoring training load and wellness in women`s college gymnastics - Leupold, O.; Cheng, J.; Wimberly, A.; Nguyen, J.; Tilley, D.; Gabbett, T. J.; Casey, E. (Sports Health: A Multidisciplinary Approach, 2025)
Background: Monitoring training load has the potential to improve sport performance and reduce injuries in athletes. This study examined training load and its association with wellness in artistic gymnastics.